2017
DOI: 10.1155/2017/5756102
|View full text |Cite
|
Sign up to set email alerts
|

Serum HMGB1 as a Potential Biomarker for Patients with Asbestos-Related Diseases

Abstract: High-mobility group box 1 (HMGB1) functions as a proinflammatory cytokine and is one of the most intriguing molecules in inflammatory disorders and cancers. Notably, HMGB1 is a potential therapeutic target and novel biomarker in related diseases. However, the diagnostic value of HMGB1 for benign and malignant asbestos-related diseases (ARDs) remains unclear. In this work, we detected preoperative serum HMGB1 levels in Chinese asbestos-exposed (AE) and ARDs populations and further evaluated the diagnostic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 46 publications
3
31
1
Order By: Relevance
“…Consistently, we found that HMGB1 levels in serum and plasma were higher in MM patients compared to healthy individuals (Figure 1) (78) and these findings were confirmed by other studies reporting significantly higher serum HMGB1 levels in MM patients compared to individuals with benign asbestos-related diseases (79,80). A systematic review and meta-analysis established HMGB1 as a prognostic marker for MM (79,81).…”
Section: High Mobility Group Box 1 Protein (Hmgb1)supporting
confidence: 87%
“…Consistently, we found that HMGB1 levels in serum and plasma were higher in MM patients compared to healthy individuals (Figure 1) (78) and these findings were confirmed by other studies reporting significantly higher serum HMGB1 levels in MM patients compared to individuals with benign asbestos-related diseases (79,80). A systematic review and meta-analysis established HMGB1 as a prognostic marker for MM (79,81).…”
Section: High Mobility Group Box 1 Protein (Hmgb1)supporting
confidence: 87%
“…However, HMGB1 can also be released from activated immune cells present in inflamed tissues; this may explain the association between HMGB1 levels in serum and the presence of extra-muscular autoimmune manifestations, such as RP, joint disease and ILD. Previous studies have demonstrated elevated HMGB1 in the serum and/or broncho-alveolar fluid of IIM-related ILD and other inflammatory fibrotic lung conditions (Ebina et al, 2011;Shu et al, 2016;Ying et al, 2017;Shimizu et al, 2018). These results support a clinical role for measuring serum HMGB1 levels; this could supplement muscle biopsy in the subtyping of IIM and, potentially, screening for IIM-related ILD (Shu et al, 2016).…”
Section: Discussionsupporting
confidence: 66%
“…A reliable panel of biomarkers is greatly needed to better quantify the MM risk deriving from EE. Potential biomarker candidates include those reviewed herein and others, such as high mobility group box 1, which has been shown to be a reliable biomarker of asbestos exposures in animal studies 77,78 and whose clinical value for predicting asbestos exposure and identifying those asbestos-exposed patients in whom mesothelioma has developed is currently under investigation, 79 as well as new biomarkers emerging from discovery studies using a proteomic approach. 80 Because a small sample of MM cases are associated with EE, pooled studies may provide an alternative to overcome this challenge and help identify features that are typical of EE.…”
Section: Recommendations and Next Stepsmentioning
confidence: 99%